Women, Motherhood and Living with HIV/AIDS
XXII, 314 p.
Keywords: There are about 34 million people worldwide living with HIV/AIDS. Half are women. There has been a dramatic global increase in the rates of women living with HIV/AIDS. Among young women, especially in developing countries, infection rates are rapidly increasing. Many of these women are also mothers with young infants. When a woman is labeled as having HIV, she is treated with suspicion and her morality is being questioned. Previous research has suggested that women living with HIV/AIDS can be affected by delay in diagnosis, inferior access to health care services, internalized stigma and a poor utilization of health services. This makes it extremely difficult for women to take care of their own health needs. Women are also reluctant to disclose their HIV-positive status as they fear this may result in physical feelings of shame, social ostracism, violence, or expulsion from home. Women living with HIV/AIDS who are also mothers carry a particularly heavy burden of being HIV-infected. This unique book attempts to put together results from empirical research and focuses on issues relevant to women, motherhood and living with HIV/AIDS which have occurred to individual women in different parts of the globe. The book comprises chapters written by researchers who carry out their projects in different parts of the world, and each chapter contains empirical information based on real life situations. This can be used as evidence for health care providers to implement socially and culturally appropriate services to assist individuals and groups who are living with HIV/AIDS in many societies. The book is of interest to scholars and students in the domains of anthropology, sociology, social work, nursing, public health & medicine and health professionals who have a specific interest in issues concerning women who are mothers and living with HIV/AIDS from cross-cultural perspective.